FORMALIZATION AND ORGANIZATIONAL AGILITY IN QUICK SERVICE RESTAURANTS IN PORT HARCOURT, RIVERS STATE (American Journal of Business Management, Economics and Banking, 2024)
This study investigates the interplay between formalization and organizational agility, focusing on how varying levels of formalization impact agility across different sectors. The research aims to address the challenges organizations face in balancing formalization with the need for agility in fast-paced environments. A cross-sectional research design was adopted, with data collected from staff members of three Quick Service Restaurants (QSRs) in Port Harcourt. The sample size was determined using Taro Yamane’s formula, and data were gathered through structured questionnaires. Reliability was assessed using Cronbach Alpha, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the hypotheses. The findings reveal a positive relationship between formalization and organizational agility measures (sense, decision-making and act agility respectively), suggesting that appropriate formalization levels can enhance agility rather than inhibit it. This relationship highlights the potential of leveraging formalization as a supportive framework for agile practices. The study recommends that organizations should strike a balance between formalized processes and the need for flexibility to foster an environment that supports rapid decision-making and innovation. The findings contribute to the understanding of how formalization can be aligned with agile methodologies to improve organizational performance and responsiveness in dynamic business environments.